Intestinal failure in adults: Recommendations from the ESPEN expert groups. Issue 6 (December 2018) - Pironi, Loris; Corcos, Olivier; Forbes, Alastair; Holst, Mette; Joly, Francisca; Jonkers, Cora; Klek, Stanislaw; Lal, Simon; Blaser, Annika Reintam; Rollins, Katie E.; Sasdelli, Anna S.; Shaffer, Jon; et al.
Summary: Background & aims: Intestinal failure (IF) is defined as "the reduction of gut function below the minimum necessary for the absorption of macronutrients and/or water and electrolytes, such that intravenous supplementation is required to maintain health and/or growth". Functionally, it may be classified as type I acute intestinal failure (AIF), type II prolonged AIF and type III chronic intestinal failure (CIF) The ESPEN Workshop on IF was held in Bologna, Italy, on 15–16 October 2017 and the aims of this document were to highlight the current state of the art and future directions for research in IF. Methods: This paper represents the opinion of experts in the field, based on current evidence. It is not a formal review, but encompasses the current evidence, with emphasis on epidemiology, classification, diagnosis and management. Results: IF is the rarest form of organ failure and can result from a variety of conditions that affect gastrointestinal anatomy and function adversely. Assessment, diagnosis, and short and long-term management involves a multidisciplinary team with diverse expertise in the field that aims to reduce complications, increase life expectancy and improve quality of life in patients. Conclusions: Both AIF and CIF are relatively rare conditions and most of the published work presents evidence from small, single-centre studies. Much remains to be investigated to improve the diagnosis and management of IF and future studies should rely on multidisciplinary, multicentre and multinational collaborations that gather data from large cohorts of patients. Emphasis should also be placed on partnership with patients, carers and government agencies in order to improve the quality of research that focuses on patient-centred outcomes that will help to improve both outcomes and quality of life in patients with this devastating condition.